A New Algorithm for the Available Transfer Capability Determination. (5th July 2010) - Busan, Stendley; Othman, Muhammad Murtadha; Musirin, Ismail; Mohamed, Azah; Hussain, Aini
Abstract : This paper presents a fast and accurate method to determine the available transfer capability. Ralston's method is used to predict the two trajectory points of voltage magnitude, power flow, and maximum generator rotor angle difference. Then, the cubic spline interpolation technique is used to accurately trace the P-V, P-S, or P- Δ δ curves between two points of trajectory. The P-V, P-S and P- Δ δ curves represent as the variations of voltage magnitude, power, flow and maximum generator rotor angle difference due to the increase of power transfer. The actual available transfer capability value is determined at the intersection point between the curve and the constraints limit. The effectiveness of the proposed method is verified by referring to the results of ATC for a case study of 2737-Polish system and 39-New England bus system. The proposed method gives satisfactorily accurate and fast computation of ATC as compared to recursive AC power flow method.